The interaction between genotype and maternal nutritional environments affects tomato seed and seedling quality - Geshnizjani, Nafiseh; Khorami, Saadat Sarikhani; Willems, Leo A J; Snoek, Basten L; Hilhorst, Henk W M; Ligterink, Wilco (Oxford University Press, 2019)
Seed and seedling traits are affected by the conditions of the maternal environment, such as light, temperature, and nutrient availability. In this study, we have investigated whether different maternally applied nitrate and phosphate concentrations affect the seed and seedling performance of two closely related tomato species: Solanum lycopersicum cv. Money maker and Solanum pimpinellifolium accession CGN14498. We observed large differences for seed and seedling traits between the two species. Additionally, we have shown that for nitrate most of the seed and seedling traits were significantly affected by genotype–environment interactions (G×E). The effect of the maternal environment was clearly visible in the primary metabolites of the dry seeds. For example, we could show that the amount of γ-aminobutyric acid (GABA) in Money maker seeds was affected by the differences in the maternal environments and was positively correlated with seed germination under high temperature. Overall, compared with phosphate, nitrate had a larger effect on seed and seedling performance in tomato. In general, the different responses to the maternal environments of the two tomato species showed a major role for G×E in shaping seed and seedling traits.
Keywords: Genotype by environment interaction (G×E); maternal environment; metabolites; seedling quality; seed quality; Solanum lycopersicum; Solanum pimpinellifolium; Taverne